Christ and the covenant: Francis Turretin's federal theology as a defense of the doctrine of Grace - Beach, James Mark (Reformed historical theology, 2007)
Cover -- Title Page -- Copyright -- Table of Contents -- Body -- Preface -- 1. Introduction -- 1.1 Francis Turretin and Federal Theology -- 1.2 The Parameters and Thesis of this Study -- 1.3 The Order and Structure of this Study -- 2. Sixteenth- and Seventeenth-Century Federal Theology and Its Interpreters -- 2.1 Introduction -- 2.2 The Diversity of Interpretation on the Rise and Development of Federal Theology -- 2.2.1 Survey of Historical Research on Federal Theology -- 2.2.2 Theological Assessments of Federal Theology